Pengalaman Ibu Usia Remaja Melahirkan Anak di Masa Pandemi COVID-19 - Padila Padila; Panzilion Panzilion; Juli Andri; Nurhayati Nurhayati; Harsismanto J (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to explore the experiences of adolescent mothers when giving birth to children during a pandemic. The research design used a qualitative type with a phenomenological approach. In this study, there were seven female adolescent participants aged 19-21 years. The instrument used was an in-depth interview guide related to the experience of childbirth during the COVID-19 pandemic. Test the validity of the data using the triangulation design technique. The results of the study found 11 themes, namely: the mother's last age and education, the definition of childbirth, the stage of childbirth, the mother's feelings during childbirth, the actions taken when the mother was anxious, treating the family for baby care, the opinion about the attitude that the family gave to the mother, the reaction of mothers in facing family treatment, patterns that mothers apply in the process of dealing with childbirth during the COVID-19 pandemic and the support young mothers receive in caring for their babies when they are sick. In conclusion, teenage mothers who gave birth during the COVID-19 pandemic suffered from moderate anxiety and lack of family support during childbirth and received treatment with poor quality access to health services. Keywords: Phenomenology, COVID-19 Pandemic, Experience, Childbirth, Adolescents